Das Hirn der Studierenden Dialogisches Lernen statt obrigkeitlicher Lehre - Günther, Klaus (Verlag Barbara Budrich, 2019)
A wide range of initiatives are aimed at the "sovereign teaching" that dominates universities and their lecture-oriented learning formats. Dissatisfied with low learning yield, dialogically designed learning processes are demanded. Klaus Günther's neurobiological perspective shows what is missing from the official learning constellation and what is possible in the dialogical learning constellation: teachers and learners meet in close communication and empathic proximity. Emotional pushing forces are generated in the learner's brain, on which the transfer of learning inputs depends on short-term memory to long-term memory. This is the only way to achieve a high learning yield - even when using digital media.